47.5k views
4 votes
Correct answer will get brainpower and +40 points! I need step by step instructions though wrong answers will get reported.

Q1: f (x) =2x - 9

Part A) Find f^-1 (3)

Part B) Find f^-1 (x)

These are the parts that need to be solved.
tysm for the help!

User Utxeee
by
6.2k points

1 Answer

5 votes

Answer:

Given :-

f (x)=2x-9

To find:-


\sf f^(-1 (3))


\sf f^(-1 (x))

Solution :-

We need to find


f^-3 \\ f^(-x)


\qquad{:}\longrightarrow\tt f^-3=2^(-3)-9


\qquad{:}\longrightarrow\tt -8-9


  • \qquad{:}\longrightarrow\tt f^(-3)=-17


\qquad{:}\longrightarrow\tt f^-x=2(-x)-9


\qquad{:}\longrightarrow\tt -2x-9

  • Multiply (-1)


\qquad{:}\longrightarrow\tt f^(-x)=2x+9

User Shamdor
by
5.9k points